PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KERJA DOSEN DI UNIVERSITAS PAWYATAN DHAHA KEDIRI - Ita Yoeli Astari (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
The terms of leadership will be more directed at how to achieve organizational targets. Many styles of leadership within the organization, but the implementation of the right to be something that a propriety. In education, transformational leadership style will be better than other leadership styles. University Pawyatan Daha Kediri abbreviated UPD is an organization implementing transformational leadership style, an institution educational organization that can push all the elements, from lecturers, students, faculty / staff, parents, local communities and others to work. The problems in this research are: (1) How does the style of leadership transformational Against Labor productivity Lecturer at the University Pawiyatan Dhaha Kediri, (2) How does the ability Work on Productivity of work Lecturer at the University Pawiyatan Dhaha Kediri, (3) How big is the influence of leadership style transformational and ability to work on Productivity of work at the University Pawiyatan Dhaha Kediri. Based on the theoretical basis that has been stated above, then the hypothesis in this study is: "It is believed there is a significant relationship and influence between transformational leadership style and ability to work on Productivity Work Lecturer at the University Pawiyatan Dhaha Kediri". The research sample as respondents as many as 65 employees. The variables used were Transformational Leadership Style, Job Skills . Work Productivity and the dependent variable . Based on tests performed by multiple linear regression, it is evident that the Transformational Leadership Style variables and variable working ability have a significant influence on the productivity of labor simultaneously (together). Then the most dominant variable in this study is the Transformational Leadership Style variables that strongly influence UPD Work Productivity lecturer in Kediri